Vibration Energy Harvesting in High-Performance Geopolymer Mortar: A Proof-of-Concept with Piezoelectric Integration - Marini, L.; Mohammad Abdul, Mannan; Ahmad Kueh, Beng Hong; Abdullah, A. A.; Abed, Farid; Gunasekaran, K.; Yonis. M, Yonis Buswig (Springer, Singapore, 2026)
The growth of global traffic demands sustainable pavement solutions, while Portland cement production contributes 7–8% of global CO2 emissions. Traffic-induced vibrations are generally dissipated, yet piezoelectric systems have the potential to harvest them into renewable electricity. This study presents a labscale proof of concept using High-Performance Geopolymer Mortar (HPGM) from industrial by-products to handle heavy loads and harsh environments, offering a medium for piezoelectric integration. Three mix groups optimized HPGM by varying fiber content, reducing anhydrous sodium silicate (ASS) with slag, or replacing ASS with liquid sodium silicate. Tests showed HPGM had high strength (up to 172.1 MPa compressive, up to 16.4 MPa flexural) and excellent durability, retaining > 93% strength with <1.2% mass loss in chemical exposure. Separately, a laboratory-scale piezoelectric system tested under footstep loading generated battery life drops as load current rises: 500 h with no load, 5.37 h with a light bulb, 50 h for phone charging (0.20 A), and 4.81 h for combined loads. The system is more efficient for low-power DC use where scaling up piezoelectric tiles could boost its renewable energy potential. These findings lay the groundwork for future integration into multifunctional pavements that combine durability, low-carbon benefits, and renewable energy harvesting from traffic-induced loads.